Effect of preharvest foliar sprays of calcium nitrate on melon fruit quality - Muñoz, Fernando Felipe (2017)
The aim of this work was to study the preharvest foliar sprays of calcium nitrate solutions and its effects on the melon quality. Melon seeds (Cucumis melo L.) cv. ´Fila´ (yellow) were used, and they were sown in multicell trays in a greenhouse. The transplant was done at the beginning of the spring 2015, when the first leaf was totally expanded. The experiment consisted of a combination of five treatments with different calcium nitrate concentration (Ca(NO3)2) and two postharvest storage environments. The calcium nitrate concentrations used were: 0.0 (control); 1.3; 2.6; 5.2 and 10.5 g L-1 Ca(NO3)2, and were supplied by foliar spraying with five applications. The postharvest storage environments were carried out using two independent chambers with temperature and humidity of: (1) 24.0 (±1.5) ºC and 6.4 (±0,8) mbar of vapor pressure deficit (VPD) and; (2) 10.0 (±0.5) ºC and 3.0 (±0.5) mbar (VPD). The fruit stored at 24ºC for 11 days had the lowest water loss with treatments 1.3 and 2.6 g L-1 Ca (NO3)2, although they did not differ from the control treatment. It was observed that at both 24°C and 10°C, the fruit that had a greater firmness corresponded to the 2.6 and 5.2 g L-1 of Ca(NO3)2 treatments, respectively. No differences were observed in total soluble solids (TSS) (P ≤ 0.05) between treatments and storage environments. The occurrence of damages by spotting of the epidermis of the fruits was observed. The severity of the damages was increasing with the Ca(NO3)2 concentration increased.